Avaliação dos eventos adversos a medicamentos em pacientes adultos internados em Hospital Universitário de Belo Horizonte - Paloma de Oliveira Farias (2019)
Background: Adverse drug events (ADE) are an important public health problem since they impact on the quality of the health service and might lead to increased mortality and reduced quality of life. Understanding patient and care factors associated with high risk of adverse events allows creating strategies to prevent the occurrence of these events. Objective: The purpose of this study was to investigate clinical and service-related factors associated with the occurrence of ADE. Methods: This analytic crosssectional study carried out at the Hospital das Clínicas (university hospital) of the Universidade Federal de Minas Gerais (UFMG) evaluated the occurrence of ADE and associated factors in adult patients (>18 years) hospitalized for more than 24 hours. A list of triggers based on the Institute of Healthcare Improvement's (IHI) Global Trigger Tool has been adapted to the local context. The search for triggers was carried out in medical records, prescriptions and through a verbal approach to health professionals. The occurrence of a trigger led to an investigation of the biological and clinical plausibility of the association between the trigger, the potential drug (s) involved, and the harm to the patient conducted in parallel by a pharmacist and an internal medicine specialist. From this analysis, these professionals confirmed or dismissed ADE. The association between the occurrence of adverse drug events (yes, no) and demographic, clinical, hospitalization and prescription factors was tested using a binomial logistic regression model. Results: The incidence of adverse events was 13.3%, and 90% were adverse reactions. The most frequent ADE were constipation (15%) and, of these, 62% were detected by means of the medical records review. The classes of drugs most frequently involved were those with action in the nervous system (30%), cardiovascular system (17%) and digestive tract and metabolism (13%). Length of stay (Odds Ratio [OR] 1.012; Confidence Interval 95% [95% CI] = 1.00-1.02), admission in intensive care unit (OR 1.53; 95% = 1.03-2.27), and the Charlson score of comorbitidities (OR 1.24; 95% CI 1,15-1,33) were significantly associated with the occurrence of ADE. Conclusion: This study suggests that patients with longer hospitalization time, greater number and severity of comorbidities at hospital admission, and need of intensive therapy along the hospitalization are at higher risk of adverse drug events. important to understand.